Energy-Efficient eHealth Monitoring with LPWAN - Guimarães, Marcelo Alves; Macêdo, Raimundo José De Araújo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2024)
This paper presents the design and development of a novel tool for collecting and transmitting clinical data over a Low Power Wide Area Network (LPWAN). The tool features custom-designed integration boards and power management mechanisms tailored explicitly for the cyclical operation of the integrated technologies. Prioritizing effective data transmission while minimizing energy consumption-a critical factor in healthcare applications-the tool employs two key strategies: (1) on/off circuitry for GPS and ECG components to conserve power, and (2) an adaptive power protocol that leverages message acknowledgments and the Received Signal Strength Indicator (RSSI) for dynamic transmission power adjustments. Real-world experiments conducted in a relatively dense environment provided valuable insights into the system's performance under realistic conditions, showing this to be a promising approach to saving energy and optimizing eHealth applications within cyber-physical distributed systems. The fully operational tool now serves as a valuable testbed for further developments in the e-health domain.